Endothelial microvesicles in hypoxic hypoxia diseases. Issue 8 (29th May 2018) - Deng, Fan; Wang, Shuang; Xu, Riping; Yu, Wenqian; Wang, Xianyu; Zhang, Liangqing
Abstract: Hypoxic hypoxia, including abnormally low partial pressure of inhaled oxygen, external respiratory dysfunction‐induced respiratory hypoxia and venous blood flow into the arterial blood, is characterized by decreased arterial oxygen partial pressure, resulting in tissue oxygen deficiency. The specific characteristics include reduced arterial oxygen partial pressure and oxygen content. Hypoxic hypoxia diseases (HHDs) have attracted increased attention due to their high morbidity and mortality and mounting evidence showing that hypoxia‐induced oxidative stress, coagulation, inflammation and angiogenesis play extremely important roles in the physiological and pathological processes of HHDs‐related vascular endothelial injury. Interestingly, endothelial microvesicles (EMVs), which can be induced by hypoxia, hypoxia‐induced oxidative stress, coagulation and inflammation in HHDs, have emerged as key mediators of intercellular communication and cellular functions. EMVs shed from activated or apoptotic endothelial cells (ECs) reflect the degree of ECs damage, and elevated EMVs levels are present in several HHDs, including obstructive sleep apnoea syndrome and chronic obstructive pulmonary disease. Furthermore, EMVs have procoagulant, proinflammatory and angiogenic functions that affect the pathological processes of HHDs. This review summarizes the emerging roles of EMVs in the diagnosis, staging, treatment and clinical prognosis of HHDs.